Situación del Trabajo Social en Castilla y León - Gómez García, Rogelio (Cuadernos de Trabajo Social, 2010)
The results of the first investigation about the professional situation of social workers in the Community of Castilla and León are shown in this survey. It is the first step towards the knowledge of tranformation in the structure and action of the profession of Social Work. This survey, thanks to the excellent work of the social workers, is focused on their sociodemographic profile, their training, their professional work and organization, among other things.
Keywords: Profession; Professionalization; Social Work; Social workers; Castilla and León